Dissemination of traditional chinese culture: a comparative analysis of Yunting and Ximalaya FM - Yunyao, Li; Hasrul Hashim (Penerbit Universiti Kebangsaan Malaysia, 2023)
Traditional Chinese culture has gradually become a trend in national mainstream media especially on new media platforms. Based on the Chinese mainstream media Yunting and the commercial audio platform Ximalaya FM, a comparative content analysis was conducted on the top 10 “humanities and history” channels on Yunting and Ximalaya FM. It was found that from the comparison between the interfaces, while both platforms had more subsections, Yunting’s humanities and history channel interface were more concise and clearer. Addressing the production teams, Yunting adopted the Professional Generated Content (PGC) mode, which was more authoritative, while Ximalaya FM adopted the Professional and User Generated Content (PUGC) mode and self-media mode. In terms of content, both platforms covered various contents, although users listened to the five topics on Yunting that were more diverse, whilst Ximalaya FM included four topics. Moreover, it was found that serialised and completed programmes were featured in the episodes. However, more drama slots were found on Ximalaya FM, while the contents released on Yunting were limited due to its status as mainstream media. In terms of listening volume, higher listening volume was recorded from Ximalaya FM due to the higher number of episodes on Ximalaya FM compared to Yunting. Overall, Yunting and Ximalaya FM each effectively played their role, guaranteeing the development of Chinese traditional culture.